Antioxidant Activity Test Combination Of Cantigi Leaf Extract (Vaccinium varingiaefolium) And Nail Henna Leaf Extract (Lawsonia inermis Linn) - Mokhamad mahroji; Shelly Taurhesia; Dian Ratih Laksmitawati (CV. Inara, 2022)
Traditionally, cantigi leaves ( Vaccinium varingiaefolium ) are used to heal wounds,swelling, burning, pain, ulcers, and function as analgesic, anti-inflammatory and antiinflammatory. inflammation, and treat fine wrinkles . henna leaves ( Lawsonia inermisLinn ) which contains glycosides, steroids, phytosterols, saponins, tannins, andflavonoids which are reported to have benefits for treating boils, scabies, headaches,back pain, and can accelerate hair growth . Cantigi leaves and fruit are reported tocontain anthocyanin compounds that function as antioxidants . while the antioxidantscontained in cantigi leaves are Beta.-mono-olein , Hexadecanoic acid, and methyl ester. The flavonoids contained in henna leaves also have the potential as antioxidants. Weare often exposed to oxidation both produced from within the body or from outside suchas pollution, cigarette smoke, UV radiation and food. Antioxidants will neutralize thesefree radicals so they do not have the ability to steal electrons from cells and DNA.Cantigi leaves and henna leaves were macerated by kinetic maceration method with70% ethanol as solvent. Antioxidants were measured using the DPPH method, thesingle extract of cantigi gave an IC 50 value of 119.23 ± 4.41 µg/mL , while the extractof a single nail henna gave an IC 50 value of 38.38 ± µg/mL. The combination ofcantigi leaf extract and nail henna leaf extract with a ratio of 1:1; 2:1 and 1:2 gavevery strong IC50 values, namely 33.84 µg/mL; 40.40 µg/mL and 29.85 µg/mL,respectively. It was concluded that the combination of cantigi leaf extract and nailhenna leaf extract with a ratio of 1:2 gave the best IC50 value of 29.85 µg/mL.